2002
DOI: 10.1046/j.1439-0426.2002.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth, reproduction and mortality of the striped seabream, Lithognathus mormyrus (Pisces, Sparidae), off the Canary Islands (Central-east Atlantic)

Abstract: Striped seabream, Lithognathus mormyrus L. (n=731) caught off the Canary Islands from January 1999 to June 2000 were studied. Fish ranged in size from 113 to 372 mm total length, weighing from 21.1 to 748.2 g total weight. Weight increased allometrically with size (b=2.9071). Fish age was 0–10‐years‐old. Growth was relatively slow (k=0.88 years−1), with females growing at a slightly faster rate than males. The species displayed protandric hermaphroditism. Male : female ratio was unbalanced in favour of males (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 24 publications
(26 reference statements)
7
41
1
2
Order By: Relevance
“…The differences are even more remarkable when one compares the results from the present study with those reported by Kraljevich et al (1995Kraljevich et al ( , 1996 for L. mormyrus from the northern Adriatic Sea and by Lorenzo et al (2002) from the centraleast Atlantic (Canary Islands). The population of L. mormyrus in the Thracian Sea reaches the same age as other populations of the Mediterranean Sea (Kraljevich et al, 1996) and of the central-east Atlantic (Lorenzo et al, 2002) but obtains a smaller size-atage. The asymptotic length (L∞) is found to be smaller than those estimated by Suau (1970), Kraljevich et al (1995Kraljevich et al ( -1996 and Lorenzo et al (2002).…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…The differences are even more remarkable when one compares the results from the present study with those reported by Kraljevich et al (1995Kraljevich et al ( , 1996 for L. mormyrus from the northern Adriatic Sea and by Lorenzo et al (2002) from the centraleast Atlantic (Canary Islands). The population of L. mormyrus in the Thracian Sea reaches the same age as other populations of the Mediterranean Sea (Kraljevich et al, 1996) and of the central-east Atlantic (Lorenzo et al, 2002) but obtains a smaller size-atage. The asymptotic length (L∞) is found to be smaller than those estimated by Suau (1970), Kraljevich et al (1995Kraljevich et al ( -1996 and Lorenzo et al (2002).…”
Section: Discussionsupporting
confidence: 57%
“…The population of L. mormyrus in the Thracian Sea reaches the same age as other populations of the Mediterranean Sea (Kraljevich et al, 1996) and of the central-east Atlantic (Lorenzo et al, 2002) but obtains a smaller size-atage. The asymptotic length (L∞) is found to be smaller than those estimated by Suau (1970), Kraljevich et al (1995Kraljevich et al ( -1996 and Lorenzo et al (2002). The growth rate (k) of the species in the Thracian Sea is relatively slow, which is in agreement with the results of the other authors (Table 8).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations